PENGARUH PENAMBAHAN FLY ASH, DODOL PLASTIK, MILLE SCALE DAN SUPERPLASTICIZER TERHADAP KUAT LENTUR BETON - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
Concrete is one of the most common construction materials used for road pavement. In pavement concrete roads are required to have good flexural strength, providing sufficient comfort for drivers and durability. To answer the demands, it is necessary to conduct research and experiment, one of the ways is by using added materials (admixture). This study aims to determine the effect of the addition of fly ash, plastic dodol, mille scale and superplasticizer to the flexural strength of concrete. Concrete is planned with fc 29.05 or K-350 with fly ash as much as 10% of cement weight, plastic waste dodol waste 0.15%, 0.25% and 0.35% of sand weight, 5% mill scale of weight of sand and superplasticizer as much as 2% of the water weight. Testing sample at age 7, 14, 28 days, to know compressive strength and flexural strength by converting from result of tensile strength of concrete and absorption.